AKTIVITAS ANTIKANKER EKSTRAK ETANOL DAUN Rhizopora mucronata TERHADAP LARVA UDANG Artemia salina Leach DAN SEL RAJI - Hartiwi Diastuti; Warsinah Warsinah; Purwati Purwati (Universitas Jenderal Soedirman, 2009)
The mangrove plant have been long used the people for traditional medicine to cure various diseases, one of them to cancer therapy. Investigation the anticancer potent of R. mucronata has not been carried yet. This research was aimed to toxicity test of R. mucronta leaf extracts againts Artemia salina Leach, then cytotoxicity test of R. mucronata leave extracts againts Raji cancer cells. The extraction of R. mucronata leaf was peformed by maseration with ethanol. The ethanol extracts was partitioned with chloroform, ethylacetate and methanol. The ethanol extracts of R. mucronata leaf respectively was examined their toxicity againts A. salina Leach larv. The toxic exctracts was examined their citotoxicity againts Raji cells. The ethanol extract of R. mucronata leaf has toxic character because has LC50 < 1000 mg/mL. Toxicity test againts A. salina and citotoxicity test againts Raji cells showed that the chloroform fraction of ethanol extract of R. mucronata leaf have highest activity, respectively IC50 value equal to 290,92 mg/mL and 105,56 mg/mL. Phytochemical study showed that the active fractions contained flavonoid, terpenoid and alkaloid.